Plant growth and yield of garlic (Allium sativum L.) under applications of liquid biofertilizers - Lana, Regina Maria Quintão; Nunes Gontijo, Luciana; Camargos de Oliveira, Roberta; Martins Magela, Mara Lúcia; Queiroz Luz, José Magno; Camargo, Reginaldo (Comunicata Scientiae, 2022)
Garlic is a highly relevant vegetable crop from the food and medicinal point of view in the culture of different peoples around the world. The new discoveries of the active components present in the bulbs increase the demand and require that garlic’s production system meets the demands of the market in quantity and quality. The nutrition in vegetables is crucial for the production and protection of crops, and in the garlic crop it is usual practice to apply minerals via leaf application during the cycle. The use and benefits of organic sources associated with minerals in the garlic crop raise questions about the viability of the leaf application method in this crop. The objective of this study was to evaluate the effectiveness of biofertilizers containing humic acids applied via leaf application in the crop of garlic (Allium sativum) in relation to the control (absence of humic acid). There was no significant variation for the foliar application of biofertilizers for the development parameters (aerial part, root system and bulb formation) and garlic production classes. Biofertilizer 4 at the dose of 30 L ha-1 stood out compared to the Biofertilizers 2 and 3 for total productivity. The use of foliar biofertilizers with organic components associated with minerals can be considered an interesting alternative for the cultivation of garlic, especially if evaluated in the long term and considering the global benefits to the cultivation system.